A Study on Body Mass Index, Physical Activity and Hypertension among Legal Practitioners (Indian Journal of Public Health Research & Development, 2023)
Background: Advocates practise for long hours with hectic work schedules. Work pressure, changing legallandscapes, uncertainty of legal cases is a great challenge to lawyers. They are unable to concentrate on their healthrelated activities. Physical inactivity causes obesity leading to risk of hypertension. In view of above issues oneof the main objectives of the study is to evaluate the relationship between physical activity, Body Mass Index andhypertension among practising advocates.Methods: A sample of 300 practising advocates at Madurai district court was selected by simple random samplingmethod. Data was collected using structured interview schedule and analysed using SPSS.Results: Nearly 90% advocates with raised body mass index were hypertensives and 68.42% advocates withinadequate physical activity developed hypertension. The difference of observation was found to be statisticallysignificant (p=0.0000).Conclusions: Practice of health fitness activities amidst busy schedule and Self- care management modifies theeffect of Body Mass Index on hypertension risk.
Keywords: Hypertension, physical inactivity, Self-care management